2018
DOI: 10.1002/bdr2.1435
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hyperglycemia and fetal cardiac development: Clinical impact and underlying mechanisms

Abstract: Congenital heart disease (CHD) is the most common type of birth defect and is both a significant pediatric and adult health problem, in light of a growing population of survivors. The etiology of CHD has been considered to be multifactorial with genetic and environmental factors playing important roles. The combination of advances in cardiac developmental biology, which have resulted in the elucidation of molecular pathways regulating normal cardiac morphogenesis, and genome sequencing technology have allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 143 publications
2
120
4
2
Order By: Relevance
“…Serum from diabetic animals with normalized glucose levels were found to be teratogenic in in vitro models . Also, numerous studies have shown that treatment with antioxidants alone are able to significantly reduce malformation rates in in vivo models, despite not having effects on hyperglycemic status . While the present study did not show a direct causal relationship between reducing oxidative stress and beneficial effects of exercise, prior studies strongly indicate that oxidative stress is a key teratogenic component leading to diabetic embryopathy …”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Serum from diabetic animals with normalized glucose levels were found to be teratogenic in in vitro models . Also, numerous studies have shown that treatment with antioxidants alone are able to significantly reduce malformation rates in in vivo models, despite not having effects on hyperglycemic status . While the present study did not show a direct causal relationship between reducing oxidative stress and beneficial effects of exercise, prior studies strongly indicate that oxidative stress is a key teratogenic component leading to diabetic embryopathy …”
Section: Discussioncontrasting
confidence: 78%
“…However, whether maternal exercise may lead to up‐regulation of endogenous antioxidants and/or, reduced ROS production due to improved mitochondrial efficiency in our model remains to be studied. Notably, eNOS‐derived NO promotes Notch signalling, cell proliferation, EMT and differentiation during heart development, and has been implicated to play a role in ROS handling . In the present study, although there was no difference in the total eNOS protein levels between all four groups, levels of phosphorylated eNOS varied, being the lowest in OMD and highest in the two groups with maternal exercise.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The mechanisms by which prenatal exposure to maternal diabetes significantly impacts fetal growth and development is complex and multifactorial. It includes epigenetic modifications, changes in the expression of genes involved in critical developmental pathways, and increased oxidative stress (reviewed in Basu and Marquez-Valdez 14,15 ). In this regard, animal models of diabetes in pregnancy have been particularly useful and necessary.…”
Section: Mechanismsmentioning
confidence: 99%
“…When broken down into specific subtypes, it is clear that some of these carry a particularly increased risk, for example, the risk of PTA is increased 14-fold (Hoang et al 2017). The mechanism by which maternal diabetes increases CHD risk is far from clear (Basu and Garg 2018). This is because it is a complex metabolic disease.…”
Section: Diabetesmentioning
confidence: 99%